The Red, Ancient and Green at the Doorstep: Qinggang Practice of "Zero-Distance Study Tour" - Xiaoguang Wang; Dawei Tian (Education Research on Study Tours and Practice, 2026)
County-level primary schools face three major difficulties in carrying out study tours: funding, transportation, and curriculum. Qinggang Minzhu Primary School is adjacent to the Ma Yuxiang Memorial Hall and the Mammoth Museum, both within a five-minute walk. Leveraging this geographical advantage, this paper proposes a "Zero-Distance Study Tour" model, constructs a "Red-Ancient-Green" three-color curriculum system, and explores four normalized implementation paths such as inter-class micro-study tours. Practice has shown that the "Zero-Distance Study Tour" model can effectively increase the participation rate of rural students in study tours and promote the social and emotional development of left-behind children. This model responds to the deployment requirements of Heilongjiang Province's "Five-Color Study Tour" initiative, specifically the inheritance of red genes and green ecological civilization education, providing a reference for similar county-level schools.